Digital Innovation for Quality Assurance in Higher Education: A Bibliometric Insight Over a Decade - Desty Hapsari Kirana; Kurnia Khafidhatur Rafiah (International Journal of Management and Business Economics, 2026)
This study aims to map the development of research on digital innovation in higher education quality assurance during 2015–2025 through a bibliometric analysis of 556 Scopus-indexed articles. The results show a significant increase in publications, especially since the COVID-19 pandemic, with a shift in focus from basic digitalization to the integration of intelligent technologies such as artificial intelligence and digital assessment in quality assurance systems. Keyword visualization reveals six main thematic clusters: higher education, COVID-19, e-learning, digitalization, digital transformation, and artificial intelligence. Citation analysis shows that the most influential literature highlights institutional digital transformation, technological readiness, online learning quality, and data-driven QA frameworks. These findings provide a comprehensive overview of the conceptual evolution and strategic challenges in strengthening digital-based quality assurance systems in higher education.